Outcomes and atrial substrate analysis in patients with HIV undergoing atrial fibrillation ablation. (16th December 2022) - Cheng, Austin; Qiu, Jessica; Barbhaiya, Chirag; Garber, Leonid; Holmes, Douglas; Jankelson, Lior; Kushnir, Alexander; Knotts, Robert; Bernstein, Scott; Park, David; Spinelli, Michael; Chinitz, Larry; et al.
Abstract: Introduction: Patients with HIV infection have increased risk of atrial fibrillation, but the pathophysiologic mechanisms and the utility of catheter ablation in this population are not well‐studied. We aimed to characterize outcomes of atrial fibrillation ablation and left atrial substrate in patients with HIV. Methods: The study was a retrospective propensity score‐matched analysis of patients with and without HIV undergoing atrial fibrillation ablation. A search was performed in the electronic medical record for all patients with HIV who received initial atrial fibrillation ablation from 2011 to 2020. After calculating propensity scores for HIV, matching was performed with patients without HIV by using nearest‐neighbor matching without replacement in a 1:2 ratio. The primary outcome was freedom from atrial arrhythmia and secondary outcomes were freedom from atrial fibrillation, freedom from atrial tachycardia, and freedom from repeat ablation, compared by log‐rank analysis. The procedures of patients with HIV who underwent repeat ablation at our institution were further analyzed for etiology of recurrence. To further characterize the left atrial substrate, a subsequent case‐control analysis was then performed for a set of randomly chosen 10 patients with HIV matched with 10 without HIV to compare minimum and maximum voltage at nine pre‐specified regions of the left atrium. Results: Twenty‐seven patients with HIV were identified. All were prescribed antiretroviral therapy at time of ablation. These patients were matched with 54 patients without HIV by propensity score. 86.4% of patients with HIV and 76.9% of controls were free of atrial fibrillation or atrial tachycardia at 1 year ( p = .509). Log‐rank analysis showed no difference in freedom from atrial arrhythmia ( p value .971), atrial fibrillation ( p ‐value .346), atrial tachycardia ( p value .306), or repeat ablation ( p value .401) after initial atrial fibrillation ablation in patients with HIV compared to patients without HIV. In patients with HIV with recurrent atrial fibrillation, the majority had pulmonary vein reconnection (67%). There were no significant differences in minimum or maximum voltage at any of the nine left atrial regions between the matched patients with and without HIV. Conclusions: Ablation to treat atrial fibrillation in patients with HIV, but without overt AIDS is frequently successful therapy. The majority of patients with recurrence of atrial fibrillation had pulmonary vein reconnection, suggesting infrequent nonpulmonary vein substrate. In this population, the left atrial voltage in patients with HIV is similar to that of patients without HIV. These findings suggest that the pulmonary veins remain a critical component to the initiation and maintenance of atrial fibrillation in patients with HIV.